Antibacterial evaluation of cotton fabrics by using novel sulfonamide reactive dyes. Issue 3 (2nd May 2017) - Gaffer, Hatem E.; Elgohary, Mohamed R.; Etman, Hassan Ali; Shaaban, Saad
Abstract : Purpose: The purpose of this paper was to synthesize novel antibacterial reactive dyes for dyeing cotton fabrics. Design/methodology/approach: Four synthetic novel antibacterial reactive dyes based on sulfonamide (D1-D4) have been synthesized by the coupling reaction of sulfonamide diazonium salt with sulfonamido-cyanurated 7-amino-4-hydroxynaphthalene-2-sulfonic acid "j-acid". The chemical structure of the synthesized dyes was secured by their spectral data [infra red (IR) and proton Nuclear magnetic Resonance (1HNMR)]. Findings: The prepared reactive dyes (D1-D4) were applied to cotton fabrics. Optimum conditions of the dying samples at sodium sulfate 100 g/l, liquor ratio (L.R.) 1:10, sodium carbonate 20 g/l at 80°C (D1, D2 and D4), 60°C (D3 for 60 min) were investigated. The fastness properties toward washing, perspiration, rubbing and light were evaluated. Dyed fabrics showed good light fastness property and good to very good washing and perspiration fastness properties according to the gray scale. Antimicrobial activities for synthesized dyes showed excellent activity against gram-negative organisms such as Pseudomonas aeruginosa and Proteus mirabilis faecalis, whereas very good activity against gram-positive organisms such as Staphylococcus aureus and Enterococcus faecalis with respect to the standard drugs ampicillin and chloramphenicol. Originality/value: The principle advantages in this study were that the synthesis of novel synthesized dyes by introducing bisulfonamide-based moieties to increase the antimicrobial activity of the cellulose fabrics could be used as a medical textile, short reaction time and reaction procedure conducted in few steps, the work up is convenient and thus the starting material can be easily prepared.